Assessing RTAs inter-regional trade enhancement in Sub-Saharan Africa - John Kagochi; Nazif Durmaz (Cogent Economics & Finance, 2018)
Regional Trade Agreements (RTAs) have been advocated as one way of securing trade liberalization by the IMF and World Bank. The study uses the gravity model of bilateral trade flows to empirically investigate the effects of RTAs on intra-regional trade on a set of 46 Sub-Saharan African (SSA) countries during 1995-2011 period. Our results indicate that three of the four selected RTAs have positive and statistically significant effect on the trade among the sub-Saharan African countries. Other included variables including distance, common language, shared border, shared colonial links, and common currency are found to be important determinants of trade among SSA countries.
Keywords: C55; F15; O50; 330; inter-regional trade; sub-Saharan Africa; RTAs